News Frames of the Russian-Ukrainian War on the Websites (Raparin Journal of Humanities (RJH), 2023)
This study aimed to reveal the news frameworks of the Russian-Ukrainian war on the (Rudaw) and (BBC) Arabic websites. The study adopted the content analysis method within the descriptive approach, as its sample consisted of all news materials published on the two websites during the first week of the war, for the period between (24/2/2022) until (2/3/2022). The total sample during the mentioned period amounted to (183) news for both sites. The study reached several results, most notably: There are statistically significant differences in the framing of the news of the Russian-Ukrainian war by the both websites. (Rudaw) focused on news briefings, while (BBC Arabic) focused on news reports in the first place. The two sites did not rely on media sources from the two sides of the conflict, while Rudaw obtained information by monitoring the accounts of senior officials of the two sides of the conflict on social media (18,55%). The results also show that the both websites depend on their correspondents and delegates in the manufacture and transmission of news with a very small percentage. While news reports were prepared by the both websites' correspondents from other countries such as the United States, Germany and Britain, not on the battlefield or on the territory of the two warring countries. With regard to the persuasive frameworks used in presenting the news, the results showed that Rudaw was more reasonable and neutral, while BBC Arabic was biased towards sympathizing with the Ukrainians and portraying them as an oppressed people. The main reason for this difference may be the reflection of the official and political position of the funder of both sites, as Rudaw refrained from any attempt to make an impact and attract the attention of the recipient, as it tried in (90,72%) of its news to convey facts and information only, leaving the decision and interpretation to the recipient. Contrasted with (BBC Arabic), which used several terms such as: occupation, invasion, crime, violations, in order to convince the public of its tendencies towards sympathy with the Ukrainians.